2012
DOI: 10.1590/s1413-86702012000300003
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effectiveness of biosimilar standard interferon versus pegylated interferon for chronic hepatitis C genotypes 2 or 3

Abstract: In patients with HCV genotypes 2 or 3 infection, a higher SVR was observed in patients receiving Peg-IFN plus RBV related to patients treated with biosimilar standard IFN plus RBV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
2
0
1
Order By: Relevance
“…Another intriguing finding from the current study was that 100% (4/4) of HCV genotype 2-infected patients achieved SVR while less than 50% (4/9) of HCV genotype 1-infected patients achieved SVR. Although the number of eligible cases examined was exceedingly small, the antiviral treatment results are similar to those previously reported for larger cohorts of patients without thrombocytopenia, 13 , 14 suggesting that splenectomy does not reduce the antiviral efficacy of IFN-based treatment.…”
supporting
confidence: 78%
“…Another intriguing finding from the current study was that 100% (4/4) of HCV genotype 2-infected patients achieved SVR while less than 50% (4/9) of HCV genotype 1-infected patients achieved SVR. Although the number of eligible cases examined was exceedingly small, the antiviral treatment results are similar to those previously reported for larger cohorts of patients without thrombocytopenia, 13 , 14 suggesting that splenectomy does not reduce the antiviral efficacy of IFN-based treatment.…”
supporting
confidence: 78%
“…Recently, a study evaluating the comparison of two treatments for patients with Hepatitis C Virus (HCV) genotypes 2 and 3 of infection, using a biosimilar standard alpha-interferon (IFN) plus ribavirin (RBV) and the second one using pegylated interferon (Peg-INF) plus RBV, was performed by researchers from the State University of Campinas (Unicamp). In this study, it was observed that the treatment with Peg-INF was more efficient on causing sustained virological response (SVR) in the patients analyzed than when the biosimilar INF was applied, concluding that, in this case, the biosimilar molecules was not the best option for the treatment of patients with HCV genotypes 2 and 3 [62].…”
Section: Biopharmaceuticals and Biosimilars In Brazilmentioning
confidence: 86%
“…Sobre lo antes mencionado, hay que señalar el hecho de que en Brasil los pacientes de genotipo no 1 solo pueden recibir Peg-IFN si presentan fibrosis avanzada, los otros solo pueden ser tratados con IFN biosimilar estándar, el cual es más barato en términos de salud pública pero ha demostrado ser peor que el Peg-IFN en eficacia. Vigani y colaboradores han demostrado que el Peg-IFN + RBV está asociado con mayores tasas de RVS cuando se compara con el IFN biosimilar estándar independientemente de la etapa de la fibrosis (79,3% versus 49,1%, p = 0,0001) (9).…”
Section: Discussionunclassified